1997
DOI: 10.1162/jocn.1997.9.6.788
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Brain Potentials Following Incorrect Feedback in a Time-Estimation Task: Evidence for a “Generic” Neural System for Error Detection

Abstract: We examined scalp-recorded event-related potentials following feedback stimuli in a time-estimation task. Six hundred msec after indicating the end of a 1 sec interval, subjects received a visual, auditory, or somatosensory stimulus that indicated whether the interval they had produced was correct. Following feedback indicating incorrect performance, a negative deflection occurred, whose characteristics corresponded closely to those of the component (the error-related negativity) that accompanies errors in cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

126
1,248
5
9

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,347 publications
(1,411 citation statements)
references
References 5 publications
126
1,248
5
9
Order By: Relevance
“…Previous research confirmed that both ERN and FRN, computed as the difference between the ERPs to negative versus positive outcomes, display highly similar EEG voltage distributions characterized by a frontal–central negative focus, sometimes a more anterior distribution for FRN (Martin & Potts, 2011; Miltner et al, 1997; Potts, Martin, Kamp, & Donchin, 2011). EEG and MEG source modeling also supported common neural generator in the dorsal anterior cingulate cortex (dACC, Keil et al, 2010; Miltner et al, 2003; Nieuwenhuis, Slagter, von Geusau, Heslenfeld, & Holroyd, 2005).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous research confirmed that both ERN and FRN, computed as the difference between the ERPs to negative versus positive outcomes, display highly similar EEG voltage distributions characterized by a frontal–central negative focus, sometimes a more anterior distribution for FRN (Martin & Potts, 2011; Miltner et al, 1997; Potts, Martin, Kamp, & Donchin, 2011). EEG and MEG source modeling also supported common neural generator in the dorsal anterior cingulate cortex (dACC, Keil et al, 2010; Miltner et al, 2003; Nieuwenhuis, Slagter, von Geusau, Heslenfeld, & Holroyd, 2005).…”
Section: Introductionmentioning
confidence: 80%
“…In the case of ERN, the outcome is communicated either by an efferent copy of the motor program (Falkenstein et al, 1995; Stahl & Gibbons, 2007) or by proprioceptive input (Holroyd & Coles, 2002), while FRN is triggered whenever the outcome information arrives via external sensory (visual, auditory, etc.) inputs (Gehring & Willoughby, 2002; Miltner et al, 1997). However, this hypothesis has received little experimental support so far.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, our finding of increased N2 could be related to the feedback-related negativity (FRN). The FRN is a negative deflection that is recorded with a peak latency of around 250 ms, elicited following an unexpected negative feedback (i.e., to an inaccurate response) (Miltner et al, 1997). Our SMS tasks were not designed to offer a feedback stimulus itself, however, it is possible that the shifted stimulus at T0 functions as a feedback signal due to its dissimilarity with the preceding tones (T-4 to T-1).…”
Section: Discussionmentioning
confidence: 99%
“…Two ERP components, the FRN and the P3, were chosen as the ERP measures of feedback processing (Donchin, Ritter, & McCallum, 1978; Gehring & Willoughby, 2002; Miltner, Braun, & Coles, 1997; Polich & Kok, 1995). The FRN is a medial frontal negativity that appears approximately 200–300 ms following feedback presentation, which is larger following monetary losses than gains (Gehring & Willoughby, 2002; Walsh & Anderson, 2012).…”
Section: Introductionmentioning
confidence: 99%